2016
DOI: 10.4103/1735-3327.187882
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary nitric oxide level in children with early childhood caries

Abstract: Background:Nitric oxide (NO), a highly reactive radical, participates in the nonspecific natural defense mechanism of the oral cavity. The present study was attempted to evaluate the salivary NO levels in 4–5 year-old children with early childhood caries (ECC). The objective of the present study was to assess the salivary NO concentration in children with different caries activity.Materials and Methods:The study included 120 healthy 4.5 year-old children and they were equally divided into three groups based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Importantly, inside the oral cavity, salivary nitrate, nitrite and the nitrate reducing capacity of the oral microbiome have been proposed to be beneficial to prevent caries 10 12 . Additionally, two weeks of nitrate-rich lettuce juice consumption improved gingival health in a recent clinical study 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, inside the oral cavity, salivary nitrate, nitrite and the nitrate reducing capacity of the oral microbiome have been proposed to be beneficial to prevent caries 10 12 . Additionally, two weeks of nitrate-rich lettuce juice consumption improved gingival health in a recent clinical study 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the antibacterial effect of NO is expressed in two ways: Prevention of bacterial growth and increase in cytotoxicity by salivary macrophages. 18 Senthil et al 19 showed that low levels of caries in children is related to increase in NO levels. Metgud et al 20 showed that extreme increase in NO can have a destructive and inflammatory effect in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, dental caries is totally preventable, being the result of a dysbiosis of the oral cavity, with both the increased presence of oral pathogens and the decreased level of protective commensals, particularly the nitrate reducing commensals. 3 The oral microbiome shifts significantly over the different time periods of child development and in response to the diet. 4 Unfortunately, the oral microbiome has had the same response as the Gut microbiome to the massive dietary shifts; the Agricultural, Industrial, and more currently, the Fast Food revolutions.…”
Section: Introductionmentioning
confidence: 99%